2016
DOI: 10.3390/md14070122
|View full text |Cite
|
Sign up to set email alerts
|

Pretrichodermamides D–F from a Marine Algicolous Fungus Penicillium sp. KMM 4672

Abstract: Three new epidithiodiketopiperazines pretrichodermamides D–F (1–3), together with the known N-methylpretrichodermamide B (4) and pretrichodermamide С (5), were isolated from the lipophilic extract of the marine algae-derived fungus Penicillium sp. KMM 4672. The structures of compounds 1–5 were determined based on spectroscopic methods. The absolute configuration of pretrichodermamide D (1) was established by a combination of modified Mosher′s method, NOESY data, and biogenetic considerations. N-Methylpretricho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 20 publications
2
45
0
Order By: Relevance
“…This is analogous to the pattern of activity seen with 2 and its analogues. While mechanistic studies were not performed with N-methylpretrichodermamide B ( 19 ), 23 we hypothesize that given the similarities in structure and IC 50 values to 2 , 19 may have the same mechanism of action and that the pretrichodermamide may be a precursor of 2 , ultimately leading to DNA damage. This hypothesis is supported by the facile conversion of pretrichodermamide A to trichodermamide A, as previously demonstrated by Seephonkai et al 25 Further studies will be necessary to elucidate the exact mechanism of DNA damage induced by 2 and determine whether 2 or its related compounds are suitable for in vivo antitumor studies.…”
Section: Resultsmentioning
confidence: 99%
“…This is analogous to the pattern of activity seen with 2 and its analogues. While mechanistic studies were not performed with N-methylpretrichodermamide B ( 19 ), 23 we hypothesize that given the similarities in structure and IC 50 values to 2 , 19 may have the same mechanism of action and that the pretrichodermamide may be a precursor of 2 , ultimately leading to DNA damage. This hypothesis is supported by the facile conversion of pretrichodermamide A to trichodermamide A, as previously demonstrated by Seephonkai et al 25 Further studies will be necessary to elucidate the exact mechanism of DNA damage induced by 2 and determine whether 2 or its related compounds are suitable for in vivo antitumor studies.…”
Section: Resultsmentioning
confidence: 99%
“…[81] Anyway, this strain produced several new unusual compounds which exhibited cytotoxic and antioxidant properties. [41,43] Marine fungi of Vietnamese coastal waters have not been explored, and this field in the marine fungal natural products chemistry began to develop thanks the expeditions.…”
Section: Discussionmentioning
confidence: 99%
“…N-methylpretrichodermamide B (107) showed cytotoxic activity against human prostate cancer cells of the 22Rv1 line, which are resistant to targeted hormone therapy. [41] In addition, the known 6-methylcurvulinic acid (108), anserinone B (109), (+)-formylanserinone B (110), 3,5-dimethyl-8-methoxy-3,4-dihydro-1H-isochromen-6-ol (111) and quinolactacide (112) were isolated from this strain and tested for cytotoxic, hemolytic and radical-scavenging activities. Anserinone B (109) and formylanserinone B (110) showed toxicity against Ehrlich carcinoma cells with EC 50 values of 46.1 and 35.7 μM, respectively, and the isochromene derivative 111 scavenged DPPH free radicals by 35 %.…”
Section: Microfilamentous Fungimentioning
confidence: 99%
“…[ 18 ], and a marine algicolous fungus ( Penicillium sp. KMM4672) [ 19 ]. All three studies showed that compound 32 , which contains chlorine, exhibited significant cytotoxicity, wherein it reduced the viability of L5178Y mouse lymphoma cells, human prostate cancer 22Rv1 cells, PC-3 cells, LNCaP cells, and brine shrimps (IC 50 = 2, 0.51, 5.11, 1.76, and 4.8 μM, respectively; while kahalalide F, docetaxel, and colchicine were employed as positive controls with IC 50 values of 4.3, 0.013, 0.015, 0.004, and 8.1 μM, respectively).…”
Section: Alkaloidsmentioning
confidence: 99%